2020
DOI: 10.1038/s41438-020-0262-z
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic and transcriptomic analysis reveals reallocation of carbon flux from cuticular wax into plastid membrane lipids in a glossy “Newhall” navel orange mutant

Abstract: Both cuticle and membrane lipids play essential roles in quality maintenance and disease resistance in fresh fruits. Many reports have indicated the modification of alternative branch pathways in epicuticular wax mutants; however, the specific alterations concerning lipids have not been clarified thus far. Here, we conducted a comprehensive, timeresolved lipidomic, and transcriptomic analysis on the "Newhall" navel orange (WT) and its glossy mutant (MT) "Gannan No. 1". The results revealed severely suppressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 55 publications
1
32
0
Order By: Relevance
“…As the outmost layer exposed to the environment, cuticle covers plant aerial organs and protects plant tissues against enormous environmental challenges such as dehydration, excessive UV radiation, mechanical damage, and even pathogen infections, which have been summarized in prior reviews [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. In addition to its protective roles, cuticle also gets involved in regulating plant development [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the outmost layer exposed to the environment, cuticle covers plant aerial organs and protects plant tissues against enormous environmental challenges such as dehydration, excessive UV radiation, mechanical damage, and even pathogen infections, which have been summarized in prior reviews [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. In addition to its protective roles, cuticle also gets involved in regulating plant development [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering that β-ketoacyl-CoA synthase (KCS) is the rate-limiting enzyme in the VLCFA elongation process and determines the carbon chain distribution of wax components, we first analyzed the expression of all 16 KCS family genes based on previous transcriptome data [ 32 ] ( Supplementary Fig. S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the high heterozygosity, long juvenile phase and difficulty in transgenic processes have largely hindered the validation of such regulatory mechanisms, and there are only a limited number of reports on the biosynthesis of anthocyanins and carotenoids based on natural mutants [ 29 31 ]. Over the past decade, although several glossy citrus mutants have been analyzed by integrated transcriptome and metabolome analysis, the findings are mainly focused on the description of wax-deficient phenotypes, influence on plastid membrane lipids and defense against fungal pathogens [ 15 , 32 , 33 ]. In this study, by comparing “Newhall” navel orange (WT) with its glossy mutant (MT), in which the elongation of VLC acyl-CoAs above C 20 is blocked, we identified a wax biosynthesis enzyme, CsKCS20, which can catalyze the elongation process to form C 22 and C 24 VLCFAs and plays important roles in carbon chain distribution and cuticular wax biosynthesis in citrus fruit.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies on the glossy surface of the ‘Newhall’ navel orange mutant demonstrated that the decrease in aliphatic wax components such as aldehydes, alkanes, alcohols, and fatty acids was related to its glossy phenotype ( Liu et al, 2015 ; He et al, 2019 ). Another study found that the plastid lipids (including monogalactosyldiacylglycerols, digalactosyldiacylglycerols, and lysophosphatidylglycerols) and the phospholipid precursors (including phosphatidic acids and DAGs) were highly accumulated in the glossy mutant ( Wan et al, 2020 ). Although HP fruit possessed glossy peel, it showed a decrease in the lipids, particularly the LysoPCs and LysoPEs in the peel and flesh, compared with those in RA fruit.…”
Section: Discussionmentioning
confidence: 99%